1999
DOI: 10.1086/302538
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Biallelic and Microsatellite Y-Chromosome Polymorphisms to Infer Affinities among African Populations

Abstract: To define Y-chromosome haplotypes, we studied seven biallelic polymorphic sites. We combined data with those from four dinucleotide-repeat polymorphisms, to establish Y-chromosome compound superhaplotypes. Eight biallelic haplotypes that matched the dendrogram proposed by other investigators were identified in 762 Y chromosomes from 25 African populations. For each biallelic site, coalescence time of lineages carrying the derived allele was estimated and compared with previous estimates. The "ancestral" haplot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 42 publications
(75 reference statements)
11
81
1
Order By: Relevance
“…The haplogroup most commonly observed in this study was HG1, which is known to be the most common in Western Europe [7], and has been recently found at appreciable frequencies also in some populations from sub-Saharan Africa [18]. We observed frequencies of HG1 higher than 50% in populations from Southern Spain, Asturias, France, and Denmark.…”
Section: Geographical Distribution Of Haplogroupssupporting
confidence: 68%
See 3 more Smart Citations
“…The haplogroup most commonly observed in this study was HG1, which is known to be the most common in Western Europe [7], and has been recently found at appreciable frequencies also in some populations from sub-Saharan Africa [18]. We observed frequencies of HG1 higher than 50% in populations from Southern Spain, Asturias, France, and Denmark.…”
Section: Geographical Distribution Of Haplogroupssupporting
confidence: 68%
“…In Africa, HG25.2 is observed in 29% of Arabs and 71% of Berbers from Morocco, but is not found in those Ethiopian populations in which a high frequency of the ancestral HG25.1 is observed (R. Scozzari and associates, unpublished results [18]). Outside Northern Africa, HG25.2 was seen at generally low frequencies in Spain, France, and Italy, although no traces could be detected in the Near East.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haplogroup E-DYS271, which accounts for 470% of the Y chromosomes in most of the populations south of the Sahara, is found on an average at a frequency of 2-3% in Northern Africa, whereas haplogroups J-M304, E-M81, and E-M78, which on the whole account for 50-90% of the northern African male-specific region of the Y chromosome (MSY) gene pool, have been only rarely observed in west/central sub-Saharan Africa. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] A group of chromosomes of potential interest to past trans-Saharan connections is the paragroup R1b1* (R-P25*). Cruciani et al 18 found this paragroup (at that time defined as haplogroup 117, or R-M173*(xSRY 10831 , M18, M73, M269)) to be present at high frequencies (up to 95%) in populations from northern Cameroon.…”
Section: Introductionmentioning
confidence: 99%